Work-Family Conflict, Enrichment, and Adolescent Academic Adjustment in Dual-Earner Family - Wang, Xiaoli; Zhang, Lijin; Wu, Xiujuan; Zhao, Min (Frontiers in Psychology, 2021)
There is ample evidence that work-family conflict (WFC) and work-family enrichment (WFE), respectively, have detrimental and beneficial impacts on the functioning of couples, families, and children. In this study, cross-sectional data from 2,136 dual-earner families in China, including parents and their children (51.2% girls, ages: 11.6–19.3 years), were used together with Actor-Partner Interdependence Model-Structural Equation Modeling (APIM-SEM) to test the hypothesis that work-family spillover can impact academic adjustment in adolescents through parental educational expectations and perceived educational expectations. The results of this analysis suggested that academic adjustment among adolescents is primarily influenced by maternal work-family experiences, such that maternal but not paternal WFC can impact academic adjustment in adolescents through parental educational expectations and perceived educational expectations. Maternal WFE was found to be indirectly associated with the academic adjustment in adolescents as a result of actual and perceived educational expectations. Additionally, we observed a significant effect of maternal WFC on the educational expectations of fathers within couple-relationship dyads. These results underscore the importance of the work-family interface as a factor that shapes the overall family health and associated outcomes, especially the importance of maternal work-family experiences in this context. Interventions that aim to promote more positive maternal work environments are thus likely to yield greater benefits for their children and families. Overall, these data indicate that work-family spillover is a core determinant of adolescent development, which warrants further study.